Strategi Pengembangan Pariwisata Situ Gede Di Kota Tasikmalaya - Adam Kartanegara; Siti Fadjarajani; Cahya Darmawan (Kilau Publishing, 2024)
Situ Gede is a natural tourist destination located in Tasikmalaya City, West Java, with great potential in the tourism sector thanks to its natural beauty and biodiversity. As the largest lake in Tasikmalaya, Situ Gede offers various tourist activities such as boating, fishing and walking around enjoying nature. However, to optimize its tourism potential, an appropriate development strategy is needed. This article aims to identify and analyze Situ Gede tourism development strategies by paying attention to aspects of sustainability, empowering local communities, and improving infrastructure and facilities. The method used in this research is a qualitative approach through literature study and interviews with relevant stakeholders, including local government, tourism industry players and local communities. The research results show that the development of Situ Gede needs to focus on improving environmentally friendly tourist facilities, better waste management, and improving the quality of human resources through training for local communities. Apart from that, more effective marketing and the development of ecotourism are also the keys to attracting tourists who care about nature conservation. With an integrated and sustainable development strategy, Situ Gede can become a leading tourist destination that supports the local economy and environmental preservation.